Abscisic acid, cold and salt stimulate conserved metabolic regulation in the moss Physcomitrella patens. (25th July 2018) - Arif, M. A.; Alseekh, S.; Harb, J.; Fernie, A.; Frank, W.
Abstract: Salt and cold are major abiotic stresses that have adverse effects on plant growth and development. To cope with these stresses and their detrimental effects plants have evolved several metabolic, biochemical and physiological processes that are mainly triggered and mediated by the plant hormone abscisic acid (ABA). To elucidate the metabolic responses of the moss Physcomitrella patens, which serves as a model plant for abiotic stress adaptation, we performed GC‐MS‐based metabolic profiling of plants challenged for 5 and 28 h with either salt, cold or ABA. Our results indicate significant changes in the accumulation of several sugars including maltose, isomaltose and trehalose, amino acids including arginine, histidine, ornithine, tryptophan and tyrosine, and organic acids mainly citric acid and malonic acid. The metabolic responses provoked by ABA, cold and salt show considerable similarities. The accumulation of certain metabolites positively correlates with gene expression data whereas some metabolites do not show correlation with cognate transcript abundance. To place our results into an evolutionary context we compared the ABA‐ and stress‐induced metabolic changes in moss to available metabolic profiles of the seed plant Arabidopsis thaliana . We detected considerable conservation between the species, indicating early evolution of stress‐associated metabolic adaptations that probably occurred at the plant water‐to‐land transition.